Local variation and regional transport of tropospheric ozone over Cape Town - Nzotungicimpaye, Claude-Michel (University of Cape Town, 2015)
Includes bibliographical references. === [Fix subscripts in abstract.] The attractive image of Cape Town is threatened by periods of poor air quality occurring most often between April and September, during episodes of brown haze. When this haze occurs, it appears in the morning as a layer of concentrated pollution, likely to be associated with photochemical pollutants such as tropospheric ozone (O3) and some of its precursors. Previous studies have identified local emission sources and meteorological conditions associated with both the air pollution and the brown haze in Cape Town. However, due to the transport of air pollutants, emissions from remote sources may also contribute to air pollution levels in Cape Town. This dissertation investigates the local variation and the regional-scale transport of atmospheric pollution over Cape Town, with a focus on O3 pollution. The study analyses O3 observations from local air quality stations and uses two atmospheric chemistry-transport models to simulate the photochemical pollution over southern Africa.